Comparative study of reading and writing levels in children with and without cognitive and visual hearing alterations (Encuentros, 2020)
This study's aimed in essence compare the levels of reading and writing in students with and without hearing, cognitive and visual disturbances, third grade EBP, of San José School from Sincelejo. A quantitative approach to research a type of comparative descriptive study was assumed, by applying tools such as ratings clinics hearing, sight and cognition, and The “Bateria de evaluación de los Procesos Lectores de los Niños de Educación Primaria (PROLEC)” made by Cuetos, Rodríguez and Ruano and the “Evaluación de Procesos de Escritura (PROESC)” also by Cuetos, to measure reading and writing variable. Probabilistic sampling was not intentional and the sample was represented in 55 children without any condition altered and 21 with cognitive, sight and hearing impairment. Statistically, an analysis of variance (ANOVA) and linear regression coefficients and compared by Mann-Whitney U test for independent samples was calculated. Processing techniques and statistical data analysis was performed using the IBM statistical package SPSS 23.0.0.0 64- 64 Bits Edition of 2015. The results   show significant differences between reading and writing, also, significant differences in some subscales both read and write (grammatical structures and Dictation pseudoword, phrases with accents and punctuation, writing an essay) are observed. It is concluded that owning a condition altered hearing, cognition and sight are not limiting to the scope the literacy’s.